História e política no Memorial de Aires, de Machado de Assis - Alcantara Filho, Wolmyr Aimberê (2009)
Commonly remembered as the last novel, the swan-song of the “wizard of Cosme Velho” , The Wager: Aires´Journal, by Machado de Assis, has been considered, in its various interpretations, as a semi-autobiographical novel. However, with the passing of time, other biases began to make their way in the critical reviews of the novel, pointing to a work that, far from being just writer´s farewell, also raised important questions, such as the role of the reader, the interstices of authorship and narration, and the possible link between literature and history. Thus, the analyses proposed by this study of the The Wager: Aires´Journal, joins the critical chain represented by Roberto Schwarz and John Gledson, that is, aims to reflect on the work of the writer in relation to issues of his time and his country. More precisely, it intends to look at the writings of counsel Aires with the same suspicion we would have with the ones from Bras Cubas and Bentinho. This is how the diary of the retired diplomat, apparently interested in homely home life facts, proves not to be at all disjointed from the public sphere. In fact, the end of the institution of slavery is a subject of the novel, that takes place between 1888 and 1889. And if the old diarist does not give due attention to the fact, even commenting that there are many other more interesting subjects in the world, it is necessary to read his comments as a representative of the common ideology of the class to which he belonged, the seignorial. Aires, this way, ends up reproducing in his speech a way of being that may not be more than one variant of the "tip of the nose" of theory of Bras Cubas. Reserved, skeptical, good listener, he still helps write a story in which the slaves did not wish to part away from the "missy" Fidelia because they feel "captive" of her affection. While possibly they just feared to starve or to be abandoned to their fate.